Occupational Therapy Approaches in Supporting Students With Sensory Disorders in Islamic Education - Fadha, Imaddudin Abil (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This research aims to identify the specific sensory needs of Students with sensory impairment in SLB 2 Bantul, design an occupational therapy intervention model aligned with Islamic education's values and principles, and evaluate this intervention model's effectiveness in improving students' participation and academic achievement. This research uses a qualitative method with a descriptive approach, where data is collected through observation, in-depth interviews, and document studies. The results showed that sensory integration therapy, structured activity planning, and neurodevelopmental treatment (NDT) were used in the therapy process, involving collaboration between teachers and parents. In conclusion, this learning and therapy helps students with special needs achieve the education curriculum's spiritual, social, knowledge, and skills aspects. This research contributes to integrating occupational therapy's perspective in the context of Islamic education in Indonesia, which has not been widely explored.